Scoliosis in a patient with lipodystrophy--treatment difficulties and literature review - Lim, H.H.; Chong, C.S. (Malaysian Medical Association, 1999)
A 12 year-old Chinese schoolgirl presented with left-sided scoliosis at the age of 9 years. She has a rare defect in lipid metabolism, which is not known to be associated with spinal deformity. Her scoliotic curve deteriorated despite bracing. We report a rare occurrence of scoliosis in patient with lipodystrophy and the difficulty of using instrumented fusion in treating this condition.